A novel approach to white-light emission using a single fluorescent urea derivative and fluoride. (29th January 2019) - Takahashi, Masaki; Enami, Yusuke; Ninagawa, Hayato; Obata, Makoto
Abstract : First observation of white fluorescence using a single fluorescent urea derivative and fluoride. Abstract : Producing white-light emission from a single fluorescent dye is particularly challenging. Herein, we report novel dual emission from a fluorescent urea derivative and tetrabutylammonium fluoride (TBAF). The dual emission is an ideal white with Commission Internationale de l'Éclairage coordinates of (0.335, 0.332) in DMSO solution and the solid mixture of the fluorescent dye and TBAF also exhibits white fluorescence.